Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning